The Importance of Pancasila Education as Learning Material in Higher Education - Sandi Arifin; Mochamad Alif Kusumah; Hesti Melati; Syaif Ali Yusrifal; Ratu Zahara Faradisha (Indonesian Journal of Educational Science and Technology, 2023)
ancasila is an extraordinary legacy from the founders of the nation which refers to noble values. There is almost no doubt, the majority of the Indonesian people are of the opinion that Pancasila is the basis of the state as well as the way of life of a plural Indonesian society that is irreplaceable. Pancasila which is accommodating to religion cannot be replaced by the ideology of secularism which is not always friendly to religion. Therefore, the restoration of the nation's collective awareness about the vital position and urgency of Pancasila in the life of the Indonesian nation state. Pancasila has again become a reference and guide in making various policies and steps, starting in religious life, humanity, nationality, democracy and justice. The Pancasila education course, which includes elements of Pancasila philosophy, is an inseparable component of the personality development course group (MKPK) in the composition of the core curriculum of tertiary institutions in Indonesia. The Pancasila Education course is a compulsory subject to be taken by every student at tertiary institutions for diploma/polytechnic and undergraduate programs. Pancasila education is designed with the intention of giving students an understanding of Pancasila as the philosophy/values of the nation, the basis of the state, and the national ideology with all its implications.